Mid- and long-term outcomes of endoscopic resection for submucosal esophageal cancer types pT1b-SM1 and pT1b-SM2 - Mora, Andres; Kawada, Kenro; Nakajima, Yasuaki; Okada, Takuya; Tokairin, Yutaka; Kawano, Tatsuyuki (Endoscopy International Open, 2019)
Background and study aims Endoscopic submucosal dissection (ESD) and endoscopic mucosal resection (EMR) are promising therapeutic options for early esophageal cancer (EC). The factors that can affect mid- and long-term survival in patients with submucosal EC (SM1 and SM2) have not been described in the literature. We aim to describe clinicopathological outcomes and factors that can affect the mid- and long-term survival in patients with resected submucosal tumors.Patients and methods We performed a retrospective analysis of patients who underwent endoscopic resection (ER) for submucosal tumors over a 20-year period. The final study population included 119 cases with 137 lesions. Information was collected according to the Japanese Classification of Esophageal Cancer 11-edition and factors affecting survival for 2 and 5 years after ER were analyzed.Results EMR was performed in 99 cases (72.3 %), ESD in 38 cases (27.7 %). There were no significant complications. Two- and 5-year survival rates were 91 % and 82 %, respectively. Mean age was 67.22 years (± 9.49 years), mortality caused by EC occurred in 13 cases (11 %). Factors that had a significant impact on long-term survival were age > 65 years (P = 0.0026), number of resected specimens (P = 0.0031), presence of another progressive disease (not EC) (P ≤ 0.001), recurrence (P = 0.0002), and relation between histopathological positive vertical margin and recurrence (P = 0.0112).Conclusions ER is viable treatment for esophageal submucosal cancer, selection between ESD/EMR can depend on tumor size and patient condition, and en bloc ER is the recommended technique for submucosal tumors. Long-term survival factors were identified.